Superoxide radical and nephrotoxic effect of cadmium exposure - Novelli, Ethel L.B. [UNESP]; Lopes, Ana M. [UNESP]; Rodrigues, Ana S. [UNESP]; Novelli Filho, José L.V.B. [UNESP]; Ribas, Bartolomé O. (Taylor & Francis, 1999)
Pollution and industrial practices result in concentrations of metals and other environmental agents that are related to environmental toxicity. Concentrations of metals are widely related to biochemicals values which are used in disease diagnosis due to environmental toxicity. This work was carried out in order to verify the nephrotoxic effect of cadmium and to clarify the contribution of reactive oxygen species (ROS) in this process. Cadmium chloride was tested for nephrotoxic damage in rats by a single intraperitoneal (i.p.) injection Cd 2+ (2 mg/kg) and oral intake (Cd2 +-100 mg/l-from CdCl 2). The cadmium-induced biochemical alterations included significant increased levels of serum creatinine concentrations, in rats with i.p. injection. Total urinary protein concentrations were only increased in rats with cadmium intake. Lipoperoxide was also increased after 3 and 7 days of the Cd 2+ treatment. No changes were observed in glutathione peroxidase activities. Cadmium-induced damage might be due to superoxide radicals (O 2 -), since Cu-Zn superoxide dismutase activities were decreased by Cd 2+ treatment. This study allows tentative conclusions to be drawn regarding which reactive oxygen metabolites play a role in cadmium nephrotoxicity. We concluded that the superoxide radical may be produced as a mediator of nephrotoxic action of cadmium.
Keywords: Cadmium; Environmental; Nephrotoxicity; Rats; Superoxide radical; cadmium; copper zinc superoxide dismutase; creatinine; glutathione peroxidase; industrial chemical; lipid peroxide; metal; protein; reactive oxygen metabolite; superoxide; animal experiment; animal model; animal tissue; concentration (parameters); creatinine blood level; enzyme activity; human; male; nephrotoxicity; pollution; protein urine level; rat; toxicity; Animalia